2015
DOI: 10.1111/cmi.12497
|View full text |Cite
|
Sign up to set email alerts
|

The toxicity of theAggregatibacter actinomycetemcomitanscytolethal distending toxin correlates with its phosphatidylinositol-3,4,5-triphosphate phosphatase activity

Abstract: The Aggregatibacter actinomycetemcomitans cytolethal distending toxin (Cdt) induces G2 arrest and apoptosis in lymphocytes and other cell types. We have shown that the active subunit, CdtB, exhibits phosphatidylinositol-3,4,5-triphosphate (PIP3) phosphatase activity, leading us to propose that Cdt toxicity is the result of PIP3 depletion and perturbation of phosphatidylinositol-3-kinase (PI-3K)/PIP3/Akt signalling. To further explore this relationship, we have focused our analysis on identifying residues that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
89
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(96 citation statements)
references
References 76 publications
(154 reference statements)
7
89
0
Order By: Relevance
“…However, as discussed earlier, Cdt binding to cells and subsequent CdtB internalization is dependent upon association and binding to cholesterol, a ubiquitous membrane component. Consistent with this finding, we have also demonstrated that Cdt binding and CdtB internalization occurs in cells that are both Cdt-susceptible as well as Cdt-resistant (Shenker et al, 2016a). Thus, restricted susceptibility to Cdt intoxication must be governed by a mechanism independent of binding and subunit internalization.…”
Section: Cdt Subunit Structure and Functionsupporting
confidence: 85%
See 3 more Smart Citations
“…However, as discussed earlier, Cdt binding to cells and subsequent CdtB internalization is dependent upon association and binding to cholesterol, a ubiquitous membrane component. Consistent with this finding, we have also demonstrated that Cdt binding and CdtB internalization occurs in cells that are both Cdt-susceptible as well as Cdt-resistant (Shenker et al, 2016a). Thus, restricted susceptibility to Cdt intoxication must be governed by a mechanism independent of binding and subunit internalization.…”
Section: Cdt Subunit Structure and Functionsupporting
confidence: 85%
“…Specifically, inhibition of the apoptotic cascade by over expression of Bcl-2 or with the use of a caspase-3 inhibitor results in suppression of the DDR with no effect on Cdt-induced cell cycle arrest. Moreover, under conditions optimized to expose cells to the minimal amount of Cdt necessary to induce maximal G2 arrest within 24 h (and apoptosis at 48 h), we were unable to demonstrate DDR activation in lymphoid cells at 4 h. DDR activation could only be induced following longer exposures to higher Cdt concentrations for both lymphocytes and HeLa cells (Shenker et al, 2016a). These results collectively argue for DDR activation, at least in lymphocytes, to be the result of late events, and likely associated with enzymatic degradation of DNA due to activation of the apoptotic cascade.…”
Section: Cdt Subunit Structure and Functionmentioning
confidence: 75%
See 2 more Smart Citations
“…In addition, A. actinomycetemcomitans produces other virulence factors such as a cytolethal distending toxin that causes apoptosis of lymphocytes [38], lipopolysaccharide (LPS)…”
Section: A Actinomycetemcomitans Has a Variety Of Virulence Factors mentioning
confidence: 99%